Till Death, Purchase of Another House, or Occurrence of Other Events Do Us Part: Interests-Oriented Fake Divorce Cases in China. Issue 2 (17th February 2019) - Fu, Ailing; Wang, Jian
ABSTRACT: Little is known about the perceptions of Chinese couples who resort to fake divorce. This study represents the results of a qualitative research on the triggers for fake divorce in China. Couples were purposefully sampled and data were collected through semi-structured, in-depth interviews. Couples dictated their own versions of causes for fake divorce, which partly corresponded with previous studies. Given that fake divorce entailed negative effects, certain suggestions were proposed. By enriching the explanations of the triggers for fake divorce and the negative effects, this study compels us to rethink the relationship between the state, policy or law, and the society in contemporary China.